KINERJA KEUANGAN, KOMISARIS INDEPENDEN, GENDER DIVERSITY DAN FINANCIAL DISTRESS - Aldama, Nabila Aprilia; Kristanti, Farida Titik (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.02.TAHUN.2022DO - 10.24843/EEB.2022.v11.i02.p01, 2022)
Large institutions have a huge influence on the economy in Indonesia, especially property, real estate, construction and building institutions because it has a significant effect on Gross Domestic Product or GDP and labor absorption. Therefore, institutions must maintain performance and financial condition in order to avoid financial distress. The purpose of this research    is to find out   the correlation of liquidity, leverage, size of institutions, independent commissioners, and gender diversity to financial distress by using quantitative techniques with secondary data. The population in   this research is property, real estate, construction and building institutions listed on the Indonesia Stock Exchange in 2014-2019, using purposive sampling techniques obtained 35 samples. The analysis method used by analysts a logistic regression by using IBM SPSS 25 application asa statistical test tool and hypothesis. The results obtained from this research show that variable liquidity, leverage, agencysize, independent commissioners, and gender diversity are simultaneously correlated to financial distress. Leverage variables are   separately negatively correlated    to financial distress while liquidity variables, company sizes, independent commissioners and gender diversity are not partially correlated to financial distress.